2014
DOI: 10.5194/acp-14-8723-2014
|View full text |Cite
|
Sign up to set email alerts
|

Observation and modelling of HO<sub>x</sub> radicals in a boreal forest

Abstract: Abstract. Measurements of OH and HO2 radicals were conducted in a pine-dominated forest in southern Finland during the HUMPPA-COPEC-2010 (Hyytiälä United Measurements of Photochemistry and Particles in Air – Comprehensive Organic Precursor Emission and Concentration study) field campaign in summer 2010. Simultaneous side-by-side measurements of hydroxyl radicals were conducted with two instruments using chemical ionization mass spectrometry (CIMS) and laser-induced fluorescence (LIF), indicating small systemat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
114
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(138 citation statements)
references
References 81 publications
13
114
4
Order By: Relevance
“…For further information please refer to Novelli et al (2014); Hens et al (2014); Martinez et al (2010). The precision for OH measurements is 4.8 × 10 5 molec cm −3 for 4 min time resolution.…”
Section: Monoterpenes Ozone Co Oh and Meteorological Parametersmentioning
confidence: 99%
“…For further information please refer to Novelli et al (2014); Hens et al (2014); Martinez et al (2010). The precision for OH measurements is 4.8 × 10 5 molec cm −3 for 4 min time resolution.…”
Section: Monoterpenes Ozone Co Oh and Meteorological Parametersmentioning
confidence: 99%
“…Firstly, the reference of Sinha et al (2008) must be an error, since that refers to a publication about the method development of the comparative reactivity method (CRM) together with first field tests conducted in the tropical rainforest of Suriname and the urban atmosphere of Mainz -but not in a boreal forest. We assume that Hens et al (2014) instead are thinking of the paper by Sinha et al (2010). Further, it is correct that Mogensen et al (2011) found a large fraction of unaccounted OH reactivity; however, they did not reach that conclusion using a box model.…”
Section: Correction On Referencementioning
confidence: 99%
“…Hens et al (2014) write "Studies on oxidation processes in monoterpene-dominated environments are rare. Direct OH reactivity measurements in a boreal forest, conducted by Sinha et al (2008), and a box model study investigating the OH reactivity budget (Mogensen et al, 2011) revealed a significant fraction of 'unknown OH reactivity'."…”
Section: Correction On Referencementioning
confidence: 99%
“…This scavenger, 3-5 sccm of pure propane in a carrier flow of 8000 sccm synthetic air for CYPHEX, was introduced through an 5 inlet pre-injector (IPI) mounted on top of the inlet nozzle (Novelli et al, 2014a;Hens et al, 2014). The scavenger amount was just sufficient to scavenge off ~95% of atmospheric OH as determined from propane titration experiments on-site.…”
Section: Hox Measurements During Cyphexmentioning
confidence: 99%
“…To minimize impact of RO2 on OH formation (Fuchs et al, 2011;Hens et al, 2014), only about 30 % of atmospheric HO2 was converted to OH using NO. The required NO flow, about 0.5 sccm pure NO in 10 sccm carrier flow during CYPHEX, was determined from titrations in ambient and calibration air.…”
Section: Hox Measurements During Cyphexmentioning
confidence: 99%